MANAJEMEN ASUHAN KEBIDANAN PADA BALITA DENGAN GIZI KURANG (LITERATURE REVIEW) - Fatmawati,; Mumthi'ah Al-Kautsar, Anieq; Alza, Nurfaizah (Jurnal Midwifery, 2022)
Introduction Malnutrition refers to deficiencies, excesses, or imbalances in a person’s intake of energy or nutrients such as protein, carbohydrates, fats, vitamins that are needed by the body. Method This literature review research aims to carry out research and obtain material resources related to midwifery care management on malnutrition infants. References such as books as well as national and international journals were used as the main resources of the research. This study was conducted by utilising a 7-stage of Varney midwifery care management approach and SOAP documentation procedure. Result Based on the various resources related to malnutrition, the findings of this research indicated that the malnutrition diagnosis could be measured by conducting a complete examination in the forms of weight and height measurement. Several problems could further occur once infants experience the lack of nutrients. The problems include malnutrition, stunting, marasmur, kwashiorkor, chronic infections, and even death. Therefore, in responding to the case of malnutrition in infants, collaboration of parents with pediatricians is needed so that parents could maintain nutritional intake and increase the weight of their babies. Conclusion This evidence-based research concludes that providing additional food for infants is significant as treatments for malnutrition infants. If infants are treated with good and healthy parenting, there will be no complication and problems related to malnutrition that will occur Therefore, it is also important for parents to be further educated related to health and proper parenting.